El barón rampante - Calvino, Italo (Biblioteca Calvino (Ediciones Siruela) ;, 2012)
A young, eighteenth-century Italian nobleman defies parental authority by adopting an exclusively arboreal life, watching from his perch in the trees the passing of the Enlightenment and participating in its various delights and duties.